PKCα and ERβ Are Associated with Triple-Negative Breast Cancers in African American and Caucasian Patients - Debra A. Tonetti; Weihua Gao; Diana Escarzaga; Kelly Walters; April Szafran; John S. Coon (International Journal of Breast Cancer)
Although the incidence of breast cancer in the United States is higher in Caucasian women compared with African American women, African-American patients have more aggressive disease as characterized by a higher percentage of triple-negative breast cancers (TNBCs), high-grade tumors, and a higher mortality rate. PKCα is a biomarker associated with endocrine resistance and poor prognosis and ERβ is emerging as a protective biomarker. Immunohistochemical analysis of ERβ and PKCα expression was performed on 198 formalin-fixed paraffin-embedded primary infiltrating ductal carcinomas from 105 African-American and 93 Caucasian patients. PKCα is positively correlated with TNBC in patients of both races and with high tumor grade in African-American patients. Patients with TNBC express less nuclear ERβ compared with all other subtypes. We find no difference in frequency or intensity of PKCα or ERβ expression between African-American and Caucasian patients. PKCα and ERβ are discussed as potential therapeutic targets for the treatment of patients with TNBC.